PENJADWALAN PEMBANGKIT HYBRID BUNAKEN DENGAN KEKANGAN KONSUMSI BAHAN BAKAR - , Galih Yudhaprawira ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Equitable utilization of electrical energy to meet the electricity needs has been done with grid interconnection. The development of stand alone generator and the hybridization have been done with renewable power. Shortages or delays in the fuel supply of conventional hybrid power systems are caused by Indonesia geographical condition. This matter encourages fuel restrictions, so that the power system can operate normally. One of the problems in the hybrid system in Indonesia is how to determine the commitment of all power in the system to serve the load power demand with emphasizing fuel consumption limit. Unit commitment problem of PLTH Bunaken system with fuel consumption limits was solved using Mixed Integer Quadratic Programming (MIQP). This study used two scenarios that represent PLTH Bunaken existing operating system and based on the optimization of fuel consumption limits. The simulation results indicate that there was an optimization chance from operation being run today. Optimization using MIQP showed that the restriction of fuel make the system capable serving all levels only when the value of PV generation is in the highest level. For the value of PV generation in the medium and low levels, high load can not be served.